Protein Content and Overrun Value in Coconut Milk-Based Ice Cream with Cashew Milk Combination - Afriana, Nerita; Kurnia, Pramudya (Newinera Publisher, 2024)
The purpose of this study is to determine the protein content and overrun value of ice cream made from a combination of coconut milk and cashew milk. This study is an experimental research with a factorial design and a research design in the form of a Complete Randomized Design (CRD). The CRD consisted of three treatments with two repetitions, using coconut milk and cashew milk in the percentages of 60:40%, 50:50%, and 50:60%. The results obtained were processed by editing, coding, tabulating, and entering data. For data analysis, a statistical test in the form of the One-Way ANOVA Test was used to determine the effect of treatment on each different formula regarding protein content and overrun value.The results showed that there was a significant difference in the use of coconut milk and cashew milk on the protein content, with a value of p=0.000 (<0.005), and the overrun value, with a value of p=0.003 (<0.005). the protein content in all ice cream samples remained below the Indonesian National Standard (SNI) minimum requirement of 2.7%. The highest protein content is ice cream A (60%: 40%) at 1.409%, followed by ice cream B (50%:50%) at 1.284%, and ice cream C (40%:60%) with the lowest protein content at 1.192%. The overrun value met the SNI (Indonesian National Standard) for industrial scale ice cream with ice cream A having an highest overrun value of 73.92%, following ice cream B with an overrun value of 65.295% meets the small industry standard, and ice cream.